Other reasons of facultative dismissal from an institute of consecrated life - Michowicz, Przemysław (Prawo Kanoniczne, 2024)
The main goal of this paper tends not so much to exemplify reasons related to dismissal of a consecrated person from its institute, which – as a task – is essentially made in search of necessity to typify them in connection with some contemporary behaviors of those members who compromise their vowes and ideals by breaking religious discipline, but rather, to problematize that kind of issue in the wilde context of all legal instruments available to major superiors in a situation that could lead to the dismissal of a member from its institute of consecrated life.